G384(P) No news isn't necessarily good news: regional experience of exception reporting by trainees. (25th October 2020) - Steadman, S; Aguirre, D; Kenyon- Blair, D; Cooper, H; O'Keeffe, M; Negrine, R; Goodyear, H; ,
Abstract : Aims: As part of a wider piece of work looking into the '8 High Impact Interventions to Improve the Working Lives of Junior Doctors' document, we gathered data on trainees' experience of how often they worked beyond their scheduled hours, then their experience of the exception reporting systems. The system is designed to allow doctors to report concerns that compromise their safety or training, to allow trusts to remedy the issues in a timely fashion. Methods: A voluntary questionnaire was designed based on the '8 High Impact Actions to Improve the Working Environment for Junior Doctors' document by NHS Improvement. This was circulated on paper at trainees' regional teaching days and online via Survey Monkey from December 2018-March 2019. Results: Responses were received from 47% (143/306) of trainees. 18% (124/136) reported working over their scheduled hours daily, 37% (50/136) reported working over hours weekly. 88% (116/132) of trainees stated they had never exception reported. Of the remainder: 4% (5/132) reported once 7% (9/132) reported some but not all the time 1% (1/132) reported every time Reasons cited for not reporting include: 'Too time consuming' (25%, 34/136) 'Nothing will change'(10%, 14/136) 'Working over hours is normal/expected' (10%, 14/136) 'Don't know how to report' (10%, 14/136) 'Worried about perceptions' (8%, 10/136) Conclusions: Based on our regional data, it is likely that exception reports submitted to trusts are only part of the picture regarding trainees working over scheduled hours. Trainees do not complete exception reports for a range of reasons as cited above. The process of exception reporting should be reviewed and culture surrounding it explored if it is to be an accurate reflection of activity. This would hopefully lead to an increase in trainees' confidence in the system and improved engagement, to facilitate its role as a tool for safe working. Regionally, this data has been fed back to RCPCH tutors to explore how they can support trainees and trusts in taking this important work forward.